Bilateral Shoulder Anterior Dislocation with Proximal Humerus Fracture After Seizure Attack Post Covid-19 Vaccine - Alrowithi, Abdullah; Marzogi, Abdullah Abdulrahman; Alsharif, Salman Salem (International Journal of Innovative Research in Medical Science, 2022)
Background: Bilateral anterior shoulder dislocation which occurred after seizure is considered rare. This case is considered unique as it was cause by seizure occurred after COVID-19 vaccination and association with fracture of the humerus. Case report: The study included 38- years old- male who is resident of Makkah city in Saudi Arabia. He is known case of schizophrenia since 2002 on clozapine 2 mg tab TID. He received Covid-19 vaccine at 11 a.m. then he got seizure attack at 8 p.m. in his home. He has bilateral shoulder severe tenderness and restricted range of motion. After that; Bilateral shoulder x-ray showing Right shoulder 3-part fracture with anterior dislocation and left shoulder greater tuberosity fracture with anterior dislocation. On 10/3/2022, he underwent open reeducation and internal fixation for the bilateral shoulder. Conclusion: Bilateral anterior dislocation of the shoulder resulting from seizure is considered rare however, it is more common than perceived. It should be considered a true orthopedic emergency condition that requires promotion of the diagnosis and management.